Islam Inklusif: Telaah Atas Doktrin dan Sejarah - Zain Abidin (Bina Nusantara University, 2013)
This work is entitled Inclusive Islam: The study of doctrine and history. This study uses hermeneutic approach (hermeneutics approach), and method used in collecting data is library research (library research). This work was motivated by a phenomenon that is now Muslims no longer perform the inclusive theology. Religion expected to bring the mercy mission to the world no longer show its role significantly. This may be due to religious thought has been contaminated by a variety of politic, economic, culture, and so forth. Now religious understanding is necessary to be reconstructed, by putting forward the spirit of togetherness and a mercy to the world. Religious understanding seems to be justified by faith, when in fact it is not; in fact,it conflicts with any religious teachings. Therefore, in this work, the author would like to show an understanding of Islam that is open, flexible, and tolerant (Islam Inclusive). Inclusive Islam is the religious understanding or insight that is open, flexible, and tolerant. Open has a meaning that Islam provides opportunities for people to criticize, if the truth or wisdom is delivered, then a tolerant religious have to accept, though of anyone or anything coming. Flexible means meaningful contact with others, without feeling awkward, and also regardless of the differences that exist, whether religion, creed, or origin. Tolerant means respecting the differences that exist, either with the same religion/belief or with a different religion/belief. Such an understanding is not only shaped by history but the doctrinal background can be found in the major source of the teachings of Islam, namely the Qur'an and the Sunnah of Prophet Muhammad SAW.